Are There Sex Differences in Knee Cartilage Composition and Walking Mechanics in Healthy and Osteoarthritis Populations?. Issue 8 (August 2015) - Kumar, Deepak; Souza, Richard B.; Subburaj, Karupppasamy; MacLeod, Toran D.; Singh, Justin; Calixto, Nathaniel E.; Nardo, Lorenzo; Link, Thomas M.; Li, Xiaojuan; Lane, Nancy E.; Majumdar, Sharmila
Abstract: Background: Women are at a greater risk for knee osteoarthritis (OA), but reasons for this greater risk in women are not well understood. It may be possible that differences in cartilage composition and walking mechanics are related to greater OA risk in women. Questions/purposes: (1) Do women have higher knee cartilage and meniscus T1ρ than men in young healthy, middle‐aged non‐OA and OA populations? (2) Do women exhibit greater static and dynamic (during walking) knee loading than men in young healthy, middle‐aged non‐OA and OA populations? Methods: Data were collected from three cohorts: (1) young active (< 35 years) (20 men, 13 women); (2) middle‐aged (≥ 35 years) without OA (Kellgren‐Lawrence [KL] grade < 2) (43 men, 65 women); and (3) middle‐aged with OA (KL > 1) (18 men, 25 women). T1ρ and T2 relaxation times for cartilage in the medial knee, lateral knee, and patellofemoral compartments and medial and lateral menisci were quantified with 3.0‐T MRI. A subset of the participants underwent three‐dimensional motion capture during walking for calculation of peak knee flexion and adduction moments, flexion and adduction impulses, and peak adduction angle. Differences in MR, radiograph, and gait parameters between men and women were compared in the three groups separately using multivariate analysis of variance. Results: Women had higher lateral articular cartilage T1ρ (men = 40.5 [95% confidence interval CI, 38.8‐42.3] ms; women = 43.3 [95% CI, 41.9‐44.7] ms; p = 0.017) and patellofemoral T1ρ (men = 44.4 [95% CI, 42.6‐46.3] ms; women = 48.4 [95% CI, 46.9‐50.0] ms; p = 0.002) in the OA group; and higher lateral meniscus T1ρ in the young group (men = 15.3 [95% CI, 14.7‐16.0] ms; women = 16.4 [95% CI, 15.6‐17.2] ms; p = 0.045). The peak adduction moment in the second half of stance was lower in women in the middle‐aged (men = 2.05 [95% CI, 1.76‐2.34] %BW*Ht; women = 1.66 [95% CI, 1.44‐1.89] %BW*Ht; p = 0.037) and OA (men = 2.34 [95% CI, 1.76‐2.91] %BW*Ht; women = 1.42 [95% CI, 0.89‐1.94] %BW*Ht; p = 0.022) groups. Static varus from radiographs was lower in women in the middle‐aged (men = 178° [95% CI, 177°‐179°]; women = 180° [95% CI, 179°‐181°]; p = 0.002) and OA (men = 176° [95% CI, 175°‐178°]; women = 180° [95% CI, 179°‐181°]; p < 0.001) groups. Women had lower varus during walking in all three groups (young: men = 4° [95% CI, 3°‐6°]; women = 2° [95% CI, 0°‐3°]; p = 0.013; middle‐aged: men = 2° [95% CI, 1°‐3°]; women = 0° [95% CI, −1° to 1°]; p = 0.015; OA: men = 4° [95% CI, 2°‐6°]; women = 0° [95% CI, −2° to 2°]; p = 0.011). Women had a higher knee flexion moment (men = 4.24 [95% CI, 3.58‐4.91] %BW*Ht; women 5.40 [95% CI, 4.58‐6.21] %BW*Ht; p = 0.032) in the young group. Conclusions: These data demonstrate differences in cartilage composition and gait mechanics between men and women in young healthy, middle‐aged healthy, and OA cohorts. Considering the cross‐sectional nature of the study, longitudinal research is needed to investigate if these differences in cartilage composition and walking mechanics are associated with a greater risk of lateral tibiofemoral or patellofemoral OA in women. Future studies should also investigate the relative risk of lateral versus medial patellofemoral cartilage degeneration risk in women compared with men. Level of Evidence: Level III, retrospective study.